Zinc Translocation from Coastal Soil to Wheat as Mediated by Zinc Supply Levels and Soil Properties - Deyong Zhao; Jie Dong; Yan Li (Plants)
The association between soil properties and zinc (Zn) availability, as well as how soil properties affect the Zn translocation from coastal soil to wheat grain, was not well understood. A pot study and field trial were conducted to examine the effects of soil properties and Zn application on grain yield and grain Zn concentration (Zn-conc) in wheat grown under coastal soils. Soil DTPA-Zn content positively correlated with concentrations of total Zn, total P, Olsen-P, and ammonia-N in soil. Zn-conc in aboveground plants negatively correlated with soil pH and Olsen-P. Total Zn accumulation (Zn-acc) in aboveground plants varied greatly among different soil treatments. Zn-acc positively correlated with soil DTPA-Zn content, Zn-conc in aboveground plants, aboveground biomass, and root weight. PLS-PM model analysis suggested that soil Zn supply and plant growth had direct effects on Zn utilization in wheat, while soil properties, soil nutrients, and soil available nutrients had indirect effects on Zn utilization in wheat by affecting soil Zn supply and/or plant growth. Grain yield and grain Zn-conc were increased by Zn application under low soil salinity, while Zn application under higher soil salinity did not increase grain Zn-conc. Soil Zn application increased both grain yield and grain Zn-conc of 20 wheat genotypes, while foliar Zn application further increased the average grain Zn-conc without an increase in grain yield. Adjusting the Zn supply tailored to suitable genotypes according to soil properties is promising to reach the Zn biofortification target and a satisfactory wheat grain yield under coastal saline soils.